Complete Septate Uterus- A Rare Occurrence Challenging Pregnancy - Pojala, Ramyapriya; Katakdhond, Shriraj (Journal of Neonatal Surgery, 2025)
A septate uterus is the most common Müllerian anomaly, often linked to reproductive challenges such as infertility and recurrent pregnancy loss. This condition results from incomplete resorption of the embryologic Müllerian ducts. Diagnostic criteria differ across medical organizations: ASRM defines a septate uterus by an indentation depth greater than 15 mm and an angle less than 90°, while ESHRE uses an indentation-to-wall-thickness (I:WT) ratio exceeding 50%. Accurate diagnosis and timely surgical intervention are crucial for improving reproductive outcomes. We present the case of a 24-year-old nulliparous female with primary infertility for three years. Clinical examination revealed a vaginal septum, confirmed by ultrasound to be a complete septate uterus with endovaginal and endocervical duplication. The patient underwent successful hysteroscopic septal resection, resulting in the removal of the uterine and cervical septa. Postoperative care included an intrauterine Foley catheter and estrogen therapy. She conceived naturally nine months post-surgery and had an uneventful recovery. Hysteroscopic septal resection remains the gold standard treatment for symptomatic septate uterus, improving pregnancy rates. Literature reports indicate a 62% pregnancy success rate post-resection. This case underscores the importance of early diagnosis and intervention to prevent adverse reproductive outcomes. Although many patients remain asymptomatic, identifying and managing a septate uterus is essential for those experiencing infertility or recurrent pregnancy loss. This report adds to the growing body of evidence supporting hysteroscopic management as an effective approach to improving reproductive potential in patients with congenital uterine anomalies.